NLRC4 inflammasome has a protective role on inflammatory bone resorption in a murine model of periodontal disease - Rocha, Fernanda R.G. [UNESP]; Delitto, Andrea E.; de Souza, Joao A Chaves; Maldonado, Laura A.G. [UNESP]; Wallet, Shannon M.; Rossa, Carlos [UNESP] (Elsevier, 2020)
There is virtually no information on the role of NLRC4 inflammasome on bone resorption and inflammation associated with periodontitis. Bacterial-associated experimental periodontitis was induced in wild-type (WT) and Nlrc4-KO C57BL/6 mice. 3 μL of a 1 × 109 UFC/mL PBS suspension of heat-killed Gram-negative bacteria were injected (3x/week for 4 weeks) directly into the gingival tissues of WT and Nlrc4-KO mice (n = 6/genotype). Control animals were injected bilaterally (3x/week for 4 weeks) in the same sites with the same volume of the PBS vehicle. Alveolar bone resorption was quantified by μCT. Inflammatory infiltrate in the gingival tissues was assessed qualitatively in H&E-stained slides and by the detection of a pan-leukocyte marker (CD45) and a neutrophil marker (Ly6G) using immunofluorescence. Modulation of Rankl, Mmp-13, Tnf-a, Il-6 and Il-10 expression in the gingival tissues was determined by RT-qPCR. Osteoclastogenesis was assessed in vivo by biochemical staining for TRAP. The relevance of NLRC4 for RANKL-induced osteoclastic differentiation and activity was investigated in vitro using bone marrow-derived macrophages from WT and Nlrc4-KO mice. Bone resorption was significantly greater in Nlrc4-KO mice; however there were no differences between WT and Nlrc4-KO mice on osteoclast numbers and on the inflammatory infiltrate. In vitro, osteoclast activity was significantly enhanced in Nlrc4-deficient macrophages; whereas RANKL-induced differentiation was not affected. Expression of the selected candidate genes was also similarly increased by the induction of experimental periodontal disease, except for the expression of Tnf-alpha and Il-10, which was already significantly higher in the gingival tissues of Nlrc4-KO mice. We conclude that NLRC4 inflammasome has a protective role on inflammatory bone resorption in this experimental model. Furthermore, the bone-sparing effect may be related with the modulation of osteoclast activity.
Keywords: Bone resorption; Inflammasomes; Inflammation; Periodontal diseases